Externalities, Monopoly and the Objective Function of the Firm - Frank Milne; David Kelsey (Queen's University, Department of Economics, 2005)
This paper provides a theory of general equilibrium with externalities and/or monopoly. We assume that the firm's decisions are based on the preferences of shareholders and/or other stakeholders. Under these assumptions, a firmrm will produce fewer negative externalities than the comparable profit maximizing firm. In the absence of externalities, equilibrium with a monopoly will be Pareto efficient if the firm can price discriminate. The equilibrium can be implemented by a 2-part tariff.
Keywords: D52; D70; L20; 330; Externality; general equilibrium; 2-part tariff; objective function of the firm